Quinazoline‐Based Hydroxamic Acids: Design, Synthesis, and Evaluation of Histone Deacetylase Inhibitory Effects and Cytotoxicity. Issue 6 (1st June 2018) - Hieu, Doan Thanh; Anh, Duong Tien; Hai, Pham‐The; Huong, Le‐Thi‐Thu; Park, Eun Jae; Choi, Jeong Eun; Kang, Jong Soon; Dung, Phan Thi Phuong; Han, Sang‐Bae; Nam, Nguyen‐Hai
Abstract : In our search for novel histone deacetylases inhibitors, we have designed and synthesized a series of novel hydroxamic acids and N ‐hydroxybenzamides incorporating quinazoline heterocycles (4a  – 4i, 6a  – 6i ). Bioevaluation showed that these quinazoline‐based hydroxamic acids and N ‐hydroxybenzamides were potently cytotoxic against three human cancer cell lines (SW620, colon; PC‐3, prostate; NCI‐H23, lung). In term of cytotoxicity, several compounds, e.g ., 4g, 4c, 4g  – 4i, 6c, and6h, displayed from 5‐ up to 10‐fold higher potency than SAHA (suberoylanilidehydroxamic acid, vorinostat). The compounds were also generally comparable to SAHA in inhibiting HDACs with IC50 values in sub‐micromolar range. Some compounds, e.g ., 4g, 6c, 6e, and6h, were even more potent HDAC inhibitors compared to SAHA in HeLa extract assay. Docking studies demonstrated that the compounds tightly bound to HDAC2 at the active binding site with binding affinities higher than that of SAHA. Detailed investigation on the estimation of absorption, distribution, metabolism, excretion, and toxicity (ADMET) suggested that compounds4g, 6c, and6g, while showing potent HDAC2 inhibitory activity and cytotoxicity, also potentially displayed ADMET characteristics desirable to be expected as promising anticancer drug candidates. Abstract :